Generalized weighted Ostrowski and Ostrowski-Gruss type inequalities on time scales via a parameter function - Kermausuor, Seth (2018)
We prove generalized weighted Ostrowski and Ostrowski–Gr ¨uss type inequalities on time scales via a parameter function. In particular, our result extends a result of Dragomir and Barnett. Furthermore, we apply our results to the continuous, discrete, and quantum cases, to obtain some interesting new inequalities